HUBUNGAN KOORDINASI MATA KAKI DAN KESEIMBANGAN TERHADAP HASIL SEPAK SILA PADA EKSTRAKURIKULER SMPN 08 KANDIS - Muhammad Ridho Gustiari; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The aim of this study is to discover and prove the relationship between eye coordination and balance on the skills of sila in extracurricular outdoor training SMP N 08 Kandis. This type of research is correlation research by looking at the relationship between eye-foot coordination and balance with the sila skills of playing sepak takraw. The independent variable is eye-foot coordination and balance, and the dependent variable is sila skill in Extracurricular High School 08 Kandis. In accordance with this type of research, correlation research (correlation research) is correlation research to determine whether there is a relationship and, if so, how close the relationship is and the meaning of the relationship (Arikunto, 2006: 270). The population in this riset was 6 extracurricular students at SMPN 08 Kandis. This study is a correlational riset in which the measurement results of two different variables are compared to determine the level of the relationship between the variables. As the independent variable eye – foot coordination (X1) and balance (X2) while the dependent variable (Y) is sila. The instrument in this study was a test with an ankle coordination test using the wall throw test with the foot, a balance test and a football test by rocking the ball for 60 seconds. Based on the results of the research described by the author in the previous chapter, it can be concluded as follows: There is a connection between eye-foot coordination with football skills, where the rtab is at a significant level α (0.05) = 0.887 means r-count (0.94)> rtab (0.878). Then there is a relationship between equilibrium with football skills, where rtab at a significant level α (0.05) = 0.878 means r count (0.98)> rtab (0.878), and there is a joint relationship between eye – foot coordination and balance with the sila capacity of extracurricular sepaktakraw -students on SMP 08 Kandis, where rtab at a significant level means α (0.05) = 0.887 means Rhitung (0.981)> rtab (0.887).Key Words : Eye-Foot Coordination, Balance, Sila, Sepak Takraw